Analisis Faktor-Faktor yang Mempengaruhi Keterlambatan Proyek Peningkatan Jalan Rel Kereta Api Medan-Binjai - Sahrial Sahrial; Irwan Irwan; Suranto Suranto (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
Seeing the construction work of a complex project, a good project management is needed such as planning, implementing activities, controling activities and scheduling a project.Where a project is said to be successful if the financing/budget is right, quality is right, and on tme. If all three categories have been met, then the project becomes a benchmark for the success of a project. We can see in the contruction of the Medan-Binjai Railroad Which is experiencing problems in the implementation of delays in the work that has been determined by he schedule. Basically, delays can be caused by all parties participating in the operation of the contruction work. In a construction project, it is not always a project that is always on time in achieving success as sheduled. The purpose of this study was to determine the factors that affect the delay in the improvement project for the Medan-Binjai Railway. The method used in data processing n this study are seven factors that greatly affect project delays, including factors due to the Covid-19 virus with a mean value of 3,62, difficulty in accessing project locations with a mean value of 3,59, lack of workforce discipline with a mean value of 3,35, the number of additional jobs wiht a mean value of 3,21, lack of skilled labor with a mean value of 3,15.